2013
DOI: 10.3390/e15093810
|View full text |Cite
|
Sign up to set email alerts
|

Entropies in Alloy Design for High-Entropy and Bulk Glassy Alloys

Abstract: High-entropy (H-E) alloys, bulk metallic glasses (BMGs) and high-entropy BMGs (HE-BMGs) were statistically analyzed with the help of a database of ternary amorphous alloys. Thermodynamic quantities corresponding to heat of mixing and atomic size differences were calculated as a function of composition of the multicomponent alloys. Actual calculations were performed for configurational entropy (S config. ) in defining the H-E alloys and mismatch entropy (S  ) normalized with Boltzmann constant (k B ), together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…A common approach has been to utilise the empirical rules of Hume-Rothery 144,145 and/or accessible thermodynamic quantities to form parametric criteria for the stability of HEA solid solutions, which are fitted to experimental results. 152,159,163,173,[203][204][205]207,[252][253][254][255][256][257][258][259][260][261][262][263][264][265][266][267] These phase-selection rules for as-cast HEAs were recently reviewed by Wang et al 258 and Guo, 208 and are discussed briefly here.…”
Section: Phase Prediction and Alloy Selection In Heasmentioning
confidence: 99%
“…A common approach has been to utilise the empirical rules of Hume-Rothery 144,145 and/or accessible thermodynamic quantities to form parametric criteria for the stability of HEA solid solutions, which are fitted to experimental results. 152,159,163,173,[203][204][205]207,[252][253][254][255][256][257][258][259][260][261][262][263][264][265][266][267] These phase-selection rules for as-cast HEAs were recently reviewed by Wang et al 258 and Guo, 208 and are discussed briefly here.…”
Section: Phase Prediction and Alloy Selection In Heasmentioning
confidence: 99%
“…Some thermodynamic parameters have been used to define the conditions for the formation of BMG or a solid solution in multicomponent alloys such as ∆H mix , ∆S mix and topological parameters like δ [35,36]. Zhang et al [36] have shown that simple solid solutions will form in alloys if −20 ≤ ∆H mix ≤ 5 kJ/mol, 12 ≤ ∆S mix ≤ 17.5 J/K mol, and δ ≤ 6.4%.…”
Section: Thermodynamic Parameters For the Formation Of Solid Solutionmentioning
confidence: 99%
“…For the considered example, a regular solid solution model has been considered to simplify the calculation for free energy of multi-component HEAs. Therefore, enthalpy of mixing for Al 35 Li 20 Mg 35 Ti 5 Zn 5 alloy with five elements can be determined from Equation (7):…”
Section: Theoretical Aspects and Designing Of A Lwheamentioning
confidence: 99%
See 1 more Smart Citation
“…HE-BMGs are considerably different from conventional H-E alloys in points that former three alloys have larger and negative ¦H mix and larger ¤ values than the latter alloys in zone S. This is due to the facts that the Al 0. 22) with the help of the plots of 6150 ternary amorphous alloys in the ¦H mix ¤ diagram. The statistical analysis revealed that the Al 0.5 TiZrPdCuNi H-E alloy has a set of ¦H mix and ¤ values where the amorphous alloys are less formed in the ¦H mix ¤ diagram, which is similar to zone S for H-E alloys Fig.…”
Section: ¹1mentioning
confidence: 99%